Performance-Based Structural Compensation Model for Structural Officials in Private Universities (A Case Study of Universitas Kristen Indonesia Toraja) - Ade Lisa Matasik; Oktavianus Pasoloran (Politeknik Siber Cerdika Internasional, 2026)
Background: Remuneration systems in private universities often lack transparency and performance-based incentives, leading to perceived inequity among structural officials—those in formal academic and managerial leadership positions. At Universitas Kristen Indonesia Toraja (UKI Toraja), the existing compensation system is primarily determined by position classification and length of service, without systematically evaluating the actual complexity and responsibilities of each role. This administrative approach fails to reflect genuine contributions, thereby undermining motivation, internal equity, and institutional competitiveness. Objective: This study aims to develop a performance-based remuneration model for structural officials in private universities through a case study at Universitas Kristen Indonesia Toraja. Methods: A qualitative case study was conducted at Universitas Kristen Indonesia Toraja through document analysis, semi-structured interviews, and a limited confirmatory questionnaire. Data were analyzed using thematic analysis following Corbin and Strauss, with triangulation across interview, documentary, and questionnaire data sources to enhance validity. Results: The findings indicate that the application of the Factor Evaluation System (FES) is relevant for objectively assessing positions based on responsibilities and work complexity rather than personal attributes. The adaptation of the nine FES dimensions results in a more holistic assessment of academic and managerial roles in private universities. The nine-level scoring system (1–9) improves fairness, transparency, and accuracy in job grading and strengthens the linkage between performance and compensation. Conclusion: The adaptive FES model constitutes a strategic instrument for merit-based human resource governance in private universities. It offers a replicable framework for institutions seeking to align structural compensation with performance, responsibility, and institutional values.